Factors affecting cellulose dissolution of oil palm empty fruit bunch and kenaf pulp in NaOH/urea solvent - Khairunnisa Waznah Baharin,; Sarani Zakaria,; Ellis, Amanda V.; Noraini Talip,; Hatika Kaco,; Sinyee Gan,; Farrah Diyana Zailan,; Sharifah Nurul Ain Syed Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The factors responsible for the low solubility percentage of oil palm empty fruit bunch (OPEFB) cellulose pulp compared to kenaf when dissolved in aqueous NaOH/urea solvent system was reported. Physical and chemical properties of both cellulose pulp were studied and compared in terms of the lignin content, viscosity average molecular weight (Mη), crystallinity index (CrI), cellulose pulp structure and their zero span tensile strength. The structure of both OPEFB and kenaf cellulose pulp were characterized using high powered microscope and field emission scanning electron microscopy (FESEM) assisted by ImageJ® software. The results show that the most significant factor that affected the OPEFB and kenaf cellulose dissolution in NaOH/-urea solvent was the Mη with OPEFB having a higher Mη of 1.68×105 compared to 5.53 × 104 for kenaf. Overall, kenaf cellulose appeared to be produced in higher quantities presumably due to its lower molecular weight with superior tensile strength and permeability in comparison to OPEFB.